Post-implementation Review of the Himalaya Home Care Project for Home Isolated COVID-19 Patients in Nepal - Amatya, Rakchya; Mishra, Kritika; Karki, Kshitij; Puri, Isha; Gautam, Archita; Thapa, Sweta; Katwal, Urmila; Veer, Siddhesh; Zervos, John; Kaljee, Linda; Prentiss, Tyler; Zenlea, Kate; et al. (Frontiers in Public Health, 2022)
Background: The emergence of coronavirus disease 2019 (COVID-19) has resulted in a pandemic that has significantly impacted healthcare systems at a global level. Health care facilities in Nepal, as in other low- and middle-income countries, have limited resources for the treatment and management of COVID-19 patients. Only critical cases are admitted to the hospital resulting in most patients in home isolation. Methods Himalaya Home Care (HHC) was initiated to monitor and provide counseling to home isolated COVID-19 patients for disease prevention, control, and treatment. Counselors included one physician and four nurses. Lists of patients were obtained from district and municipal health facilities. HHC counselors called patients to provide basic counseling services. A follow-up check-in phone call was conducted 10 days later. During this second call, patients were asked about their perceptions of the HHC program. Project objects were: (1) To support treatment of home isolated persons with mild to moderate COVID-19, decrease burden of hospitalizations, and decrease risks for disease transmission; and, (2) To improve the health status of marginalized, remote, and vulnerable populations in Nepal during the COVID-19 pandemic. Results Data from 5823 and 3988 patients from May 2021-February 2022 were entered in initial and follow-up forms on a REDCap database. The majority of patients who received counseling were satisfied. At follow-up, 98.4% of respondents reported that HHC prevented hospitalization, 76.5% reported they could manage their symptoms at home, and 69.5% reported that counseling helped to limit the spread of COVID-19 in their household. Conclusions Telehealth can be an essential strategy for providing services while keeping patients and health providers safe during the COVID-19 pandemic.